2 - Knowledge is Power and Power Affects Knowledge: Challenges for Research Collaboration in and with Africa - Melber, Henning (Africa Development, 2021)
This article engages with the challenges facing genuine research collaboration and knowledge production in a North–South interaction. It maps the asymmetries in global knowledge production in general and revisits African realities in particular. Using the experiences of the Norwegian research programme NORGLOBAL as an empirical reference point, it critically explores the limitations of partnerships and identifies some challenges resulting from the centuries of Northern hegemony established in all spheres related to global affairs and interactions. It presents some thoughts and suggestions as to how these limitations might be reduced or eliminated in favour of a truly joint effort to meet the challenges on the way towards equal relations and mutual respect.